Jane Austen's men : rewriting masculinity in the romantic era - Ailwood, Sarah (New York, NY : Routledge, 2020)
"This book illuminates Jane Austen's exploration of masculinity through the courtship romance genre in the socially, politically and culturally turbulent Romantic era. Austen scrutinises, satirises, censures and ultimately rewrites dominant modes of masculinity through the courtship romance plot between her heroines and male protagonists. This book reveals that Austen pioneers and celebrates a new vision of masculinity that could complement the Romantic desire for agency, individualism and selfhood embodied in her heroines. Rewriting desirable masculinity as an internalised, psychologically complex and authentic gender identity - a model of manhood that drives the ongoing appeal and cultural power of her men in the twenty-first century - Austen explores both the challenges and the opportunities for male selfhood, romantic love and feminine agency. Jane Austen's Men is among the first full-length works to explore Austen's male protagonists as textual constructions of masculinity. Sarah Ailwood reveals the depth of Austen's engagement with her predecessors and contemporaries, including Mary Wollstonecraft, Jane West and Jane Porter, on critical questions of masculinity and its relationship to femininity and narrative form. This book illuminates in new ways Jane Austen's ambitions for the novel, and the political power of the courtship romance genre in the Romantic era." --
Chapter One . The men of "real Life": Educating the Reader in Sense and Sensibility -- Chapter Two. "I will prove myself a man": Northanger Abbey -- Chapter Three. "A man violently in love": Pride and Prejudice -- Chapter Four. "You will make him everything": Masculine Redemption in Mansfield Park -- Chapter Five. "A disgrace to the name of man": Emma, the National Tale and the Historical Novel -- Chapter Six. "Feelings glad to burst their usual restraints": Persuasion -- Conclusion: Sanditon, Unfinished Work and New Directions.
OCLC-licensed vendor bibliographic record.
Keywords: Austen, Jane, -- 1775-1817 -- Characters; Austen, Jane, -- 1775-1817 -- Criticism and interpretation; Men in literature; Masculinity in literature; Courtship in literature; Romanticism -- Great Britain; LITERARY COLLECTIONS / General; LITERARY CRITICISM / General